Osteogenesis of Mesenchymal Stem Cells Derived from Bone Marrow in vitro - Hussein, Shalal M; Salih, Shahlaa M; Younis, Sally T (Al-Nahrain Journal of Science, 2018)
This study was designed to evaluate osteogenic potential of mesenchymal stem cells (MSCs) isolated from mouse bone marrow in vitro. MSCs were isolated through collecting the thigh bone (femur and tibia). Cells were flushed from bones and MSCs isolated based on the ability of adherence to plastic surfaces. Reactivity MSCs to CD105 and CD34 were tested by immunocytochemistry. Isolated MSCs exhibited positive reactivity to CD105 and negative for the haematopoietic surface marker CD34. Differentiation of isolated MSCs into osteoblast was induced by osteogenic medium consisting of high glucose- Dulbecco’s Modified Eagle Medium (DMEM) supplemented with 50 µg /ml Ascorbic acid, 1nM dexamethasone and10 Mm of beta glycerophosphate disodium salt hydrate after 21 days. Osteoblast activity was monitored by evaluation alkaline phosphatase (ALP) activity in osteogenic medium by Reflotron at (0, 7, 14 and 21) days of differentiation. Results recorded that a significant increase in Alkaline phosphatase activity in osteogenic medium at 7 and 14 day culture in comparison with zero day and decreased at 21 day.